1,1'-binaphthyl-based chiral materials : our journey - Pu, Lin, 1965- (Imperial College Press ; Distributed by World Scientific Pub. Co., 2010)
Chiral materials have been studied in the Department of Chemistry at the University of Virginia for applications in areas like asymmetric catalysis, enantioselective fluorescent sensing, and optical/electrical materials. Optically active 1,1'-binaphthyl molecules are used to build novel chiral polymers, dendrimers, macrocycles, and acyclic molecules. 1,1'-Binaphthyl molecules are chosen because of their remarkably stable chiral configuration as well as their high asymmetric inductions in many processes. In this book, both the fundamental knowledge about the 1,1'-binaphthyl molecules and the synthesis of the structurally diverse 1,1'-binaphthyl-based materials are described. The applications of these materials in various fields are also discussed. This book will serve as a reference for graduate students as well as other professionals working in the related fields.